Airborne Position and Orientation System for Aerial Remote Sensing - Jianli Li; Jiancheng Fang; Zhaoxing Lu; Lijian Bai (International Journal of Aerospace Engineering)
The airborne Position Orientation System (POS) can accurately measure space-time reference information and plays a vital role in aerial remote sensing system. It may be applied in a direct georeference system for optical camera and a motion imaging system for Synthetic Aperture Radar (SAR), which further advances efficiency and quality of imaging sensors. In this paper, the operation principle and components of airborne POS are introduced. Some key technologies of airborne POS are summarized. They include the error calibration and compensation, initial alignment, lever arm error modeling, time synchronization, and integrated estimation method. A high precision airborne POS has been developed and applied to a variety of aerial remote sensing systems.